SAPAAN HONOROFIK UNTUK “ORANG TUA’ BERDASARKAN JARAK SOSIAL DALAM BAHASA BANJAR - Rissari Yayuk (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
The title of this research is honorofik Greetings to the "parent" based on social distance in Bahasa Banjar. Issues raised is how to use a form of greeting honorofik "Parent" in Banjar and how to use the greeting based on social distance in Banjar language. This study is intended to descriptive honorofik greetings to the "parent" by social distance in Bahasa Banjar type is descriptive qualitative research. Techniques used in data collection and documentation is recording technique. researchers took three areas that are considered to represent that Banjar Regency, Banjarbaru and Banjarmasin. Time data capture for six months, namely January 1, 2015 sd March 1 2015. The studies suggest the use of a form of greeting honorofik intention to "parent" contained in the Banjar people from within the community Banjar include greeting old Anggah'Orang Datu ', Datu'Datu', Kai'kakek '/ nini'nenek', Abah'Bapak '/ mama'Ibu'. The use of a form of greeting is realized based on the social scale consists of two things, which consists of 1) Use of Greetings Based Social Relations in Society 2) Use of Greetings Based on Age in Family Relations.